Divine Hiddenness and Christian Theism: A Biblical Theodicy - Price Randall J. (Perichoresis: The Theological Journal of Emanuel University, 2023)
This article offers a Christian response to J.L. Schellenberg’s argument for atheism from divine hiddenness. Utilizing the unique theological features of the Christian tradition, I aim to show that Schellenberg’s argument does not undermine belief in Christian theism. The first half of the article focuses on differences between the theological presuppositions of classical theism and those assumed in Schellenberg’s use of perfect being theology. In the remainder of the article, I present a biblical theodicy that pulls from the Old Testament and current trends in religious belief to argue that the experience of divine hiddenness should not be unexpected if Christianity it true.